Decreased Laminin Expression by Human Lung Epithelial Cells and Fibroblasts Cultured in Acellular Lung Scaffolds from Aged Mice - Godin, Lindsay M. (PLoS One, 2016)
The lung changes functionally and structurally with aging. However, age-related effects on the extracellular matrix (ECM) and corresponding effects on lung cell behavior are not well understood. We hypothesized that ECM from aged animals would induce aging-related phenotypic changes in healthy inoculated cells. Decellularized whole organ scaffolds provide a powerful model for examining how ECM cues affect cell phenotype. The effects of age on ECM composition in both native and decellularized mouse lungs were assessed as was the effect of young vs old acellular ECM on human bronchial epithelial cells (hBECs) and lung fibroblasts (hLFs). Native aged (1 year) lungs demonstrated decreased expression of laminins α3 and α4, elastin and fibronectin, and elevated collagen, compared to young (3 week) lungs. Proteomic analyses of decellularized ECM demonstrated similar findings, and decellularized aged lung ECM contained less diversity in structural proteins compared to young ECM. When seeded in old ECM, hBECs and hLFs demonstrated lower gene expression of laminins α3 and α4, respectively, as compared to young ECM, paralleling the laminin deficiency of aged ECM. ECM changes appear to be important factors in potentiating aging-related phenotypes and may provide clues to mechanisms that allow for aging-related lung diseases.